Analisis Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor - Sirojudin Maljum, Ahmad (Universitas Dian Nuswantoro, 2024)
This research was conducted with the aim of examining the effect of Bleaching Motor Vehicle Tax, Exemption of Transfer Fee for Motor Vehicles, Socialization of Taxation and Online Tax Payments on Motor Vehicle Taxpayer Compliance at the SAMSAT Semarang I Office. Motor Vehicle Tax is the largest income of the provincial government so this is necessary maximized so that taxpayers obey to pay their obligations, one of the efforts that can be done by the provincial government is by procuring a program for the cancellation of motor vehicle tax fines and the exemption of motorized vehicle transfer fees. This needs to be supported by effective outreach and good service to make it easier for taxpayers to pay taxes, one of which is by making online tax payments. This research uses a quantitative type, namely with a questionnaire as a research instrument. The population in this study were 100 SAMSAT Semarang I taxpayers with accidental sampling as the data collection strategy. The tests used include: descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression analysis and hypothesis testing. The results of this study indicate that the Bleaching of Motor Vehicle Taxes, Exemption of Transfer Fees for Motor Vehicles and Tax Socialization have a significant effect on Motor Vehicle Taxpayer Compliance, while Online Tax Payments have no significant effect on Motor Vehicle Taxpayer Compliance at SAMSAT Semarang I.